Imaging of shoulder disorders. Issue 3 (June 2022) - Fawcett, Richard; Rowbotham, Emma
Abstract: The radiological evaluation of shoulder disorders has evolved to incorporate virtually all imaging modalities. This article discusses the varying roles of these modalities and includes key points for understanding the indications, diagnostic value, and limitations of each. Plain radiography, ultrasound, computed tomography, and magnetic resonance imaging (including magnetic resonance arthrography) are discussed, as well as recent innovations in these fields. The optimum imaging method for the diagnosis of specific shoulder pathologies, such as fracture, rotator cuff tendon disease and arthropathy, is discussed, while incorporating useful advice on diagnostic accuracy and availability from the radiologist's perspective. The purpose is to give an overview and a general approach to the imaging diagnosis of shoulder disorders to inform current and future orthopaedic practice.